Salvage of failed trapeziectomy, ligament reconstruction and tendon interposition with suture button suspensionplasty for basilar joint arthritis. Issue 2 (March 2019) - Yang, Kai; Graf, Alexander; Kim, Nicholas; Sanger, James; Matloub, Hani
Abstract : Background: Thumb basilar joint arthritis is a common pathology treated by hand surgeons. Trapeziectomy followed by various reconstructive techniques have been described; however, treatment options after failed primary trapeziectomy and ligament reconstruction (LRTI) with painful subsidence are not well studied. Suture button suspensionplasty has emerged as a new primary reconstructive procedure in recent years. We aim to report our experience of using suture button suspensionplasty as a salvage procedure for patients presenting with recurrent painful subsidence after primary surgical intervention. Methods: A retrospective chart review of all patients undergoing suture button suspensionplasty between 2016-2017 was performed. Patients who had the procedure after failed primary trapeziectomy and LRTI were included in the study. Patient demographic data, diagnostic imaging, clinical presentation, operative details, surgical pathology, and clinical outcomes were reviewed. Results: Thirty-two button suspensionplasties were performed in the 2-year span. Five patients underwent surgery for failure of previous trapeziectomy with ligament reconstruction. All patients had Eaton stage III arthritis at original presentation. The average age was 59 yr. Average follow-up was 13 mo (11-18 mo). All patients reported significant improvement in pain and hand function after revision surgery. One patient had a second revision surgery because of failure of the first revision secondary to a fall. Postoperative Disabilities of Arm Shoulder and Hand (DASH) score range from 13.3 to 25, with an average of 19.8. Conclusions: Suture button suspensionplasty is a viable option for patients who present with painful subsidence after failure of primary surgical intervention for basilar joint arthritis.